2014
DOI: 10.1099/jmm.0.075895-0
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and microbiology of Shiga toxin-producing Escherichia coli other than serogroup O157 in England, 2009–2013

Abstract: Epidemiology and microbiology of Shiga toxin-producing Escherichia coli other than serogroup O157 in England, 2009England, -2013

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
63
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 21 publications
3
63
1
Order By: Relevance
“…This strain does not possess the pathogenicity factor intimin and the stx2a shiga-toxin subtype which are known to be associated with more severe disease and progression to haemolytic-uraemic syndrome (HUS) [3]. Previous clusters have mainly been travel-associated and limited to around three cases [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This strain does not possess the pathogenicity factor intimin and the stx2a shiga-toxin subtype which are known to be associated with more severe disease and progression to haemolytic-uraemic syndrome (HUS) [3]. Previous clusters have mainly been travel-associated and limited to around three cases [1].…”
Section: Discussionmentioning
confidence: 99%
“…Such misidentifications are detected when strains are referred for confirmation and typing at the GBRU. Since December 2012, a small number of laboratories, including services in Brighton and central London have adopted polymerase chain reaction (PCR) techniques to detect verocytotoxin genes in stool samples, resulting in an increased number of diagnoses of non-O157 VTEC, including serogroup O117 [3].…”
Section: Discussionmentioning
confidence: 99%
“…The National Reference Laboratory for Enteropathogenic Bacteria (NRL) at the Norwegian Institute of Public Health (NIPH) receives presumptive STEC isolates for verification and characterisation from all the Norwegian medical microbiological laboratories. Historically, laboratories have identified STEC by culturing, with focus on the identification of O157 [3, 11]. In the years following the 2006 outbreak, a majority of medical microbiological laboratories in Norway implemented PCR detection of stx .…”
Section: Introductionmentioning
confidence: 99%
“…via animal contact is less well known. Contact with farm and domestic animals has been identified as a risk factor for VTEC non-O157 [74,75] and Y. enterocolitica, respectively [76]. While the evidence is less clear for L. monocytogenes, transmission from animal to human is plausible, as Listeria has been identified in pet food [77], urban poultry flocks [78] and at least one study identified living on a cattle farm as an increased risk of listeriosis [79].…”
Section: Discussionmentioning
confidence: 99%